Hybrid Perceptions. Rethinking Phenomenology and Semiotics Through Actor-Network-Theory - Padoan, Tatsuma (E|C, 2023)
It is generally acknowledged that Latour, through his work in STS and his use of concepts borrowed from Paris School semiotics, has given a fundamental contribution to rethinking the status of objects in social sciences. However, while using semiotic mod els, Latour decided to leave out of the picture the phenomenological approach developed in Greimas s later semiotic contributions, and in the work of many of his successors. Among the reasons for this choice, he mentioned the incapacity of phenomenology to escape a divide between Subjects and Objects, based on a narrow focus on human intentionality. In my paper I wish to return to this issue concerning ANT and phenomenology, and propose to invert the phenomenological paradigm, by rethinking it through a sem io narrative syntax, i.e. the narrative logic underlying the organisation of actants. Instead of inscribing semiotics within a phenomenology of perception, I will show how the opposite path might be more fruitful, especially when the human or nonhuman natu re attributed to subjects and objects is a priori undecidable, and only emerges from discourse and actantial interactions, manifesting themselves into hybrid human nonhuman assemblages I shall discuss the implications of this reversal, by analysing the re lationships between ascetics and mountain territory, as well as between humans, deities, and artefacts, in my ethnography of ascetic pilgrim groups in Katsuragi, central Japan.